Chromium Alloyed Steel Nitriding within Close-To-Critical Temperature Range; Advanced Materials Research; Vol. 1013 : Structure and Properties of Metals at DifferentEnergy Effects and Treatment Technologies - Kovalevskaya Zh. G. Zhanna Gennadievna; Klimenov V. A. Vasily Aleksandrovich; Goncharenko I. M. Igor Mikhailovich; Ivanov Yu. F. Yuriy Fedorovich; Belousova N. S. Nataljya Sergeevna (2014, 2014)
Title screen